2007
DOI: 10.1063/1.2753717
|View full text |Cite
|
Sign up to set email alerts
|

Optical quenching of NiO∕Ni coated ZnO nanowires

Abstract: Low temperature photoluminescence (PL) measurements were carried out to investigate optical transition characteristics of ZnO nanowires, Ni nanodot, and NiO coated ZnO nanowires (NWs). PL emission spectra show emission peaks of distinctive bound exciton to neutral donor (DX0) and to acceptor (AX0) transition. The authors found that the optical quenching was drastic with increasing temperature and the activation energies are unusually small. The major PL emission peak for ZnO NW was switched from DX0 to AX0 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…If β = 0, it reduces to the Manakov system [26]. Vector solitons for the CH model have been widely studied in a number of papers [24,25,[27][28][29][30]. The existence of vector rogue waves have been demonstrated in [22,23].…”
Section: Model and MI Characteristicsmentioning
confidence: 96%
“…If β = 0, it reduces to the Manakov system [26]. Vector solitons for the CH model have been widely studied in a number of papers [24,25,[27][28][29][30]. The existence of vector rogue waves have been demonstrated in [22,23].…”
Section: Model and MI Characteristicsmentioning
confidence: 96%
“…Next to the TES peak there are peaks at 3.307 eV (3.309 eV) which are attributed to the acceptor-bound excitons (A 0 X) and at 3.255 eV (3.245 eV) attributed to the donor-acceptor pair (DAP) emission. A 0 X transition could be related to nitrogen acceptor and/or to complex that was formed due to the diffusion of Ni ions into ZnO [5]. The presence of atomic nitrogen during the growth process is confirmed by the XRD measurements where C 3 N 4 was formed in buffer film (see Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Carrier induced stable room tem-perature (RT) ferromagnetism has been predicted for transition-metal doped ZnO DMSs [1]. This prediction gave a motivation to extensive investigations ZnO based solid solutions, in particular to Ni-doped ZnO films [2], polycrystalline powders [3], nanoparticles [4], and nanowires [5,6]. In this paper we report on the growth of ZnO nanowires (NWs) on a nickel foil substrate covered with a nickel oxide (NiO) thin film by carbo-thermal method and on the studies of the properties of grown NWs with the use of scanning electron microscopy (SEM), X-ray diffractometry (XRD) measurements, and photoluminescence (PL) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the intensity decreases below 80 K which coincide with the decreasing transition energy. It is reported that surface related exciton quenches quickly with increasing temperature [22,23]. Consequently, in our case, in the temperature region where the deep level exciton transforms to the surface bound exciton, the optical recombination deactivates.…”
mentioning
confidence: 63%